Superwetting membrane-based strategy for high-flux enrichment of ethanol from ethanol/water mixture - Wei, Zhongwei; Zhang, Shaoqing; Chang, Li; Liu, Hongliang; Jiang, Lei (Frontiers in Chemistry, 2022)
Ethanol, which can be scalable produced from fermented plant materials, is a promising candidate to gasoline as the next-generation liquid fuel. As an energy-efficient alternative to distillation, membrane-based strategies including pervaporation and reverse osmosis have been developed to recover ethanol from fermentation broths. However, these approaches suffer the drawback of low separation flux. Herein, we report a superwetting membrane system to enrich ethanol from water in a high-flux manner. By synergistically regulating surface energy of the solid porous membrane and hydration between an additive inorganic potassium salt and water, concentrated ethanol can rapidly wetting and permeate the porous membrane, with the salt solution being blocked. Using this newly developed superwetting membrane system, we can achieve fast enrichment of ethanol from water, with flux of two orders magnitude higher than that of pervaporation and reverse osmosis membranes.